2020
DOI: 10.1002/adts.202000195
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Computational Characterization of 2D Compositionally Complex Transition‐Metal Chalcogenide Alloys

Abstract: 2D binary transition‐metal chalcogenides (TMCs) such as molybdenum disulfide exhibit excellent properties required for energy conversion applications. Alloying binary TMCs can form 2D compositionally complex TMC alloys (CCTMCAs) that possess remarkable properties from the constituent TMCs. High‐throughput workflow performing density functional theory (DFT) calculations based on the virtual crystal approximation (VCA) model (VCA‐DFT) is designed. The workflow is tested by predicting properties including in‐plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 159 publications
2
9
0
Order By: Relevance
“…The calculated lattice parameters are in very good agreement (less than 2% differences in general) with the existing literature for all considered pristine TMD phases 37–40 and the Janus phases of H and T′. 41–43…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The calculated lattice parameters are in very good agreement (less than 2% differences in general) with the existing literature for all considered pristine TMD phases 37–40 and the Janus phases of H and T′. 41–43…”
Section: Resultssupporting
confidence: 81%
“…The calculated lattice parameters are in very good agreement (less than 2% differences in general) with the existing literature for all considered pristine TMD phases [37][38][39][40] and the Janus phases of H and T 0 . [41][42][43] In general, the calculated lattice parameters both for MX 2 and MXY monolayers increase with the increasing atomic radius of the chalcogen atoms. It is found that the optimized b lattice parameters of pristine and Janus TMDs are very close to half of the b 0 lattice parameters for T 00 phases as the conventional unit cell for the T 00 phase is double that of other phases in the y direction.…”
Section: Resultsmentioning
confidence: 91%
“…Most of the research so far has been done on flat, 2D structures, both theoretically and experimentally. [17][18][19][20] Individual multiwalled WS 2 and MoS 2 nanotubes are having a resurgence of interest, as interesting optical and electrical properties have been reported in recent years such as quasi-1D superconductivity, [21] electroluminescence, [22] confined optical cavity modes within the nanotube core, [23,24] whispering gallery modes, [25] as well as the lowtemperature Coulomb blockade, [26] field-effect transistors, [27,28] and field emitters, [29] making them promising components for nanoelectronic devices. In recent years, TMDCs have opened a new frontier in the area of field emission devices, due to their layered structure and the presence of thin and sharp edges with high aspect ratios which enhance local electric field.…”
Section: Introductionmentioning
confidence: 99%
“…* erhart@chalmers.se All of the binary alloys based on (Mo, W)(S, Se) 2 have been synthesized [19], usually in the hexagonal H structure (spacegroup P 6m2, ITCA number 187; Fig. 1b), and have been thoroughly studied in the context of band gap engineering by composition control [18,[20][21][22][23][24][25]. It has been shown that these alloys are random at ambient conditions due to (very) small mixing energies [18].…”
Section: Introductionmentioning
confidence: 99%